Acute thromboembolic ischemic stroke in rural hospital, the role of early treatment in reducing brain damage - Munzirul Akbar; Yopie Afriandi Habibie; Mursyida Mursyida (Intisari Sains Medis, 2021)
Introduction: Stroke has a high mortality and disability rate, and the main cause of physical disability in productive age and elderly. In developed countries stroke is the number one cause of admission of patients to hospital, with a mortality proportion of 20%  within the first 28 days of treatmentCase Report: A 45-year-old man came to the neurology polyclinic of RSUD Aceh Besar on March 21st, 2021 with chief complaints of the general weakness of the left limb, complete numbness and heavy feeling in the left limb since 4 hours of before admission which is felt to be getting weaker from time to time, happened suddenly when the patient was working collecting stones. He complained of dizziness as well, and did not decrease while resting. After the attack, the patient remains conscious with no headache, no nausea and vomiting, no double images were seen. On Siriraj score showed result of -4. The patient was hospitalized with injection of Citicolin 1000 mg and then discharged 5 days later with significant improvement.Conclusion: Ischemic Stroke requires fast, precise and accurate handling to prevent and avoid disability and even death. One of the effective efforts is to organize health promotion and preventive programs starting from the First Level Health Facility (FKTP) on an ongoing basis to the community.